Detection of circulating antigens in sera of rabbits infected with Toxoplasma gondii. - Ise, Y (1985)
Experiments were performed to investigate the usefulness of an enzyme-linked immunosorbent assay utilizing avidin-biotin interaction as a diagnostic tool for detection of Toxoplasma antigen in blood. The lower limit of sensitivity of the assay by this method was ca. 4 ng/ml, and standard assays provided a linear plot of antigen concentration over a range up to 250 ng/ml. In rabbits inoculated subcutaneously with trophozoites of the RH strain, Toxoplasma antigen became demonstrable in the circulation 3 days after injection, before emergence of antibody in serum and development of parasitemia. Analysis of the antigen in serum from infected rabbits by high-permeation liquid gel chromatography suggested the occurrence of antigens of four different molecular weights, greater than or equal to 400,000, 220,000, 130,000, and 45,000. Of these antigens, those of molecular weights 220,000 and 130,000 showed a conspicuous elevation with time after infection.